2013
DOI: 10.14336/ad.2013.0400244
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Defects in Erythrocyte 2,3-Diphosphoglycerate Metabolism in Dementia

Abstract: Alzheimer disease (AD) is the most common dementing illness. Metabolic defects in the brain with aging contribute to the pathogenesis of AD. These changes can be found systematically and thus can be used as potential biomarkers. Erythrocytes (RBCs) are passive "reporter cells" that are not well studied in AD. In the present study, we analyzed an array of glycolytic and related enzymes and intermediates in RBCs from patients with AD and non-Alzheimer dementia (NA), age-matched controls (AC) and young adult cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 44 publications
2
38
0
Order By: Relevance
“…113 Consistently, reports of hemoglobin (Hgb), a major component of red blood cells known to increase blood O 2 carrying capacity by 70%, 114 was significantly decreased in the red blood cells of AD patients as compared with non-AD controls. 115 In the early stages of AD, reduced Hgb reactivity has been found in practically all the neurons containing p-tau, NFTs, and -synuclein, while Hgb expression was preserved in neighboring healthy neurons. 116 Additional studies support the important contributions of Hgb to hypoxia in AD by demonstrating its interactions with A and co-localization with vascular amyloid deposits in postmortem AD brain tissues.…”
Section: Mechanisms Of Hypoperfusion-induced Neuroinflammation Inmentioning
confidence: 91%
“…113 Consistently, reports of hemoglobin (Hgb), a major component of red blood cells known to increase blood O 2 carrying capacity by 70%, 114 was significantly decreased in the red blood cells of AD patients as compared with non-AD controls. 115 In the early stages of AD, reduced Hgb reactivity has been found in practically all the neurons containing p-tau, NFTs, and -synuclein, while Hgb expression was preserved in neighboring healthy neurons. 116 Additional studies support the important contributions of Hgb to hypoxia in AD by demonstrating its interactions with A and co-localization with vascular amyloid deposits in postmortem AD brain tissues.…”
Section: Mechanisms Of Hypoperfusion-induced Neuroinflammation Inmentioning
confidence: 91%
“…However, an uncertainty over Aβ plaques being a cause or a consequence of AD remains, although current evidence favours the former being the case [8]. This uncertainty nevertheless remains, particularly in the light of the numerous AD drug failures, the majority of which were aimed to target key pathways critical within the amyloid cascade hypothesis [14]. Like AD, Type 2 Diabetes Mellitus (T2DM) is also considered as a degenerative metabolic disease that occurs in later age, and is associated with the gradual loss of insulin secreting pancreatic beta-cells [15].…”
Section: Introductionmentioning
confidence: 99%
“…We found that in erythrocytes of elderly control subjects (AMC, age-matched controls), glycolysis and cation transport were sharply inhibited, as evidenced by a significant decrease in all glycolytic enzyme activities, a decrease in the rate of glucose consumption, ATP concentration, the rate of pyruvate and lactate formation, and a sharp decrease in Na + , K + -ATP-ase activity compared to young adult controls (YAC). In the erythrocytes of AD and NA patients, these parameters changed to the same extent and significantly exceeded the parameters not only of AMC, but also of the YAC group indicating an increase in ion fluxes leading to acceleration of RBC glycolytic pathway [198,199].…”
Section: The Possible Role Of Erythrocytes In Neuronal Aerobic Glucosmentioning
confidence: 80%
“…Thus, the cells of the AMC group were marked by disturbed homeostasis of adenine nucleotides, a slight but significant decrease in 2,3-DPG concentration [59]. Similarly, there were no differences in pro-oxidant levels [199] between AMC, AD, and NA groups, while antioxidant enzyme activity, considerably reduced in RBCs of the AMC subjects, further decreased with dementia [198].…”
Section: The Possible Role Of Erythrocytes In Neuronal Aerobic Glucosmentioning
confidence: 92%